Beetroot juice lowers blood pressure and improves endothelial function in pregnant eNOS−/− mice: importance of nitrate‐independent effects. (27th May 2020) - Tropea, Teresa; Renshall, Lewis J.; Nihlen, Carina; Weitzberg, Eddie; Lundberg, Jon O.; David, Anna L.; Tsatsaris, Vassilis; Stuckey, Daniel J.; Wareing, Mark; Greenwood, Susan L.; Sibley, Colin P.; Cottrell, Elizabeth C.
Abstract : Key points: Maternal hypertension is associated with increased rates of pregnancy pathologies, including fetal growth restriction, due at least in part to reductions in nitric oxide (NO) bioavailability and associated vascular dysfunction. Dietary nitrate supplementation, from beetroot juice (BRJ), has been shown to increase NO bioavailability and improve cardiovascular function in both preclinical and clinical studies. This study is the first to investigate effects of dietary nitrate supplementation in a pregnant animal model. Importantly, the effects of nitrate‐containing BRJ were compared with both 'placebo' (nitrate‐depleted) BRJ as well as water to control for potential nitrate‐independent effects. Our data show novel, nitrate‐independent effects of BRJ to lower blood pressure and improve vascular function in endothelial nitric oxide synthase knockout (eNOS −/− ) mice. These findings suggest potential beneficial effects of BRJ supplementation in pregnancy, and emphasize the importance of accounting for nitrate‐independent effects of BRJ in study design and interpretation. Abstract: Maternal hypertension is associated with adverse pregnancy outcomes, including fetal growth restriction (FGR), due in part to reductions in nitric oxide (NO) bioavailability. We hypothesized that maternal dietary nitrate administration would increase NO bioavailability to reduce systolic blood pressure (SBP), improve vascular function and increase fetal growth in pregnant endothelial NO synthase knockout (eNOS −/− ) mice, which exhibit hypertension, endothelial dysfunction and FGR. Pregnant wildtype (WT) and eNOS −/− mice were supplemented with nitrate‐containing beetroot juice (BRJ+) from gestational day (GD) 12.5. Control mice received an equivalent dose of nitrate‐depleted BRJ (BRJ−) or normal drinking water. At GD17.5, maternal SBP was measured; at GD18.5, maternal nitrate/nitrite concentrations, uterine artery (UtA) blood flow and endothelial function were assessed, and pregnancy outcomes were determined. Plasma nitrate concentrations were increased in both WT and eNOS −/− mice supplemented with BRJ+ ( P  < 0.001), whereas nitrite concentrations were increased only in eNOS −/− mice ( P  < 0.001). BRJ− did not alter nitrate/nitrite concentrations. SBP was lowered and UtA endothelial function was enhanced in eNOS −/− mice supplemented with either BRJ+ or BRJ−, indicating nitrate‐independent effects of BRJ. Improvements in endothelial function in eNOS −/− mice were abrogated in the presence of 25 mm KCl, implicating enhanced EDH signalling in BRJ− treated animals. At GD18.5, eNOS −/− fetuses were significantly smaller than WT animals ( P  < 0.001), but BRJ supplementation did not affect fetal weight. BRJ may be a beneficial intervention in pregnancies associated with hypertension, endothelial dysfunction and reduced NO bioavailability. Our data showing biological effects of non‐nitrate components of BRJ have implications for both interpretation of previous findings and in the design of future clinical trials. Key points: Maternal hypertension is associated with increased rates of pregnancy pathologies, including fetal growth restriction, due at least in part to reductions in nitric oxide (NO) bioavailability and associated vascular dysfunction. Dietary nitrate supplementation, from beetroot juice (BRJ), has been shown to increase NO bioavailability and improve cardiovascular function in both preclinical and clinical studies. This study is the first to investigate effects of dietary nitrate supplementation in a pregnant animal model. Importantly, the effects of nitrate‐containing BRJ were compared with both 'placebo' (nitrate‐depleted) BRJ as well as water to control for potential nitrate‐independent effects. Our data show novel, nitrate‐independent effects of BRJ to lower blood pressure and improve vascular function in endothelial nitric oxide synthase knockout (eNOS −/− ) mice. These findings suggest potential beneficial effects of BRJ supplementation in pregnancy, and emphasize the importance of accounting for nitrate‐independent effects of BRJ in study design and interpretation.